Effects of Different Parent Materials and Toposequence on status and distribution of Iron Oxides in Some Soils of Sulaymaniyah Governorate / Iraq - Alobaidy, Somaya; Essa, Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Three transects were chosen in Sulaymaniyah governorate / Iraq. The first was located within the Bazian Plain, while the second was in Sulaymaniyah plain, and the third was located within the plain of Shahrazur, in order to study the effect of parent material and toposequence on the status and distribution of Iron oxides in these soils. Results Shows that there is a differences in the amount and distribution of free iron oxides between the studied pedons, and even within one Pedon. These differences can be attributed to the effect of the difference in the parent materials and topography. Also, the soils developed on Basalt rocks and Red Mudstone were characterized by their high iron oxides and dark brown color, while those developed on Limestone rocks were characterized by their low iron oxides and yellowish brown color. The topographic location also, affected the transport of weathering products of parent rocks from elevated areas and deposed in the plain areas.